Splicing inhibition of U2AF(65) leads to alternative exon skipping - Cho, Sunghee (Proc Natl Acad Sci U S A, 2015)
U2 snRNP auxiliary factor 65 kDa (U2AF(65)) is a general splicing factor that contacts polypyrimidine (Py) tract and promotes prespliceosome assembly. In this report, we show that U2AF(65) stimulates alternative exon skipping in spinal muscular atrophy (SMA)-related survival motor neuron (SMN) pre-mRNA. A stronger 5′ splice-site mutation of alternative exon abolishes the stimulatory effects of U2AF(65). U2AF(65) overexpression promotes its own binding only on the weaker, not the stronger, Py tract. We further demonstrate that U2AF(65) inhibits splicing of flanking introns of alternative exon in both three-exon and two-exon contexts. Similar U2AF(65) effects were observed in Fas (Apo-1/CD95) pre-mRNA. Strikingly, we demonstrate that U2AF(65) even inhibits general splicing of adenovirus major late (Ad ML) or β-globin pre-mRNA. Thus, we conclude that U2AF(65) possesses a splicing Inhibitory function that leads to alternative exon skipping.